Rare Objects and the Rhapsodic World of Yoruba Elite Art Collectors: Preliminary Notes - Aderonke Adesola Adesanya (Yoruba Studies Review)
This paper is a preliminary note on the data collected during my research on archives in Nigeria in the summer of 2013. While I examined both public and private archives, I found the private archives particularly those in the cities in southwestern Nigeria to be surprisingly rich in objects that are rare, new, and sometimes with unusual subject matter. The archives belong to notable elite collectors who are the de facto shapers of the art industry in Nigeria today. Their archives are worth art-historlcal study in terms of the richness of the collectlon, and because the sites are the contemporary repositories of not only anclent art but also traditional, modern and contemporary works of art. From the range and volume of the collections, the archives seem to have taken over from the government-owned museums. The shift is very interesting to study as one traces the trajectory of art acquisition and accumulation from pre-modern to modern institutions. The preliminary submission here is that Nigerian elite art collectors are lnterveners and game changers. Their intervention could be seen in two ways: First, as rescuers of disappearing cultures and by the same platform they are pivotal to reclamation of cultural patrimony. Secondly, as game changers and transformative agencies the elite collectors become culture brokers who work assiduously to stem 'culture flight' and 'heritage drain'. The platforms they offer grant them boasting rights as art connoisseurs and promotes the affirmation of elite power within the matrix of a post-colonial nation state.